The Relationship between Adversity Quotient and Early Childhood Cognition - Abidin, Ratno; Asy’ari (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Learning activities that are less enjoyable have an impact on children's low intelligence. Even though an adversity quotient is very necessary for young children to be able to help them overcome the difficulties they are facing. So far, no research has been found that discusses the relationship between the adversity quotient and the cognitive learning outcomes of early childhood. Based on this, this research aims to analyze the relationship between the adversity quotient and the cognitive learning outcomes of early childhood. This research is a type of quantitative research with a correlation approach. Sampling was carried out using a purposive sampling method with a sample size of 38 children. The methods and instruments used to collect data are questionnaires and tests. Data were analyzed using inferential statistical analysis techniques with the help of SPSS software. The results of the research show that there is a correlation between the adversity quotient as an independent variable and student learning achievement as a dependent variable, although it is not strong. Adversity quotient contributes to the cognitive learning abilities of early childhood. Based on calculations of regression (correlation) analysis between groups of variables, it was found that the adversity quotient had a relationship with the cognitive learning outcomes of early childhood. Therefore, it can be concluded that the adversity quotient intelligence has an impact on the cognitive learning outcomes of early childhood. This research has implications for providing an understanding that the adversity quotient intelligence possessed by students needs to be improved because it affects their cognitive abilities.